Effect of Gender Discrimination on Women’s Participation in Development Activities in Bumbo Town Council, Namisindwa District - Shamimu Nabulobi (Uganda Christian University, 2024)
This research report was undertaken to examine the effect of gender discrimination on women's participation in development activities in Bumbo Town Council, Namisidwa District. It was guided by three objectives; to assess the effect of social cultural norms on women’s participation in development activities of Bumbo Town Council, to analyze the effect of gender based violence on women's participation in development activities of Bumbo Town Council, to determine the effect of economic disparities on women's participation in development activities of Bumbo Town Council. The researcher used a sample size of 63 respondents and used questionnaires and interview guide to collect data and later the data was analyzed using the statistical package for social sciences (SPSS). Results of the first objective showed that social cultural norms have a significant effect on women’s participation in development activities of Bumbo Town Council. Supported by the following responses; 54% were positive to the statement that social cultural norms often prioritize the education of boys over girls; 62% were positive to the statement that cultural expectations that prioritize women's care giving roles limit their time and resources for engaging in income-generating activities; 61% of the respondents were positive to the statement that cultural norms position women as passive participants in decision-making processes. Results of the second objective revealed that gender based violence has a significant effect on women's participation in development activities of Bumbo Town Council. Supported by the following responses; 56% of the respondents were positive to the statement that gender based violence limits women's opportunities for employment, reduces their earnings, and restricts their access to financial resources. Results of the third objective showed that economic disparities have a significant effect on women's participation in development activities of Bumbo Town Council. 75% were positive to the statement that unequal access to education and skill development opportunities due to economic disparities hinder women's capability to engage in development activities. The government should implement campaigns and workshops to educate communities about gender equality, women's rights, and the negative impact of violence against women.